Hadis Tentang Hukum Khitan Perempuan (Kajian Sanad dan Matan) - Sayyidah, Nurma (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2018)
Circumcision is a tradition known and observed by societies form different religious tradiions worldwide. In Indonesia, especially on Muslim community, this tradition is deeply rooted. Having been observed for not only male but also female Muslims, its practice gains controversy. They who refuse its practice to women argue that female circumcision, while it is banned by WHO, it causes negative effects to women reproductive health. This paper attempts to examine hadith reports commonly used by Indonesian Muslims as the basis for legitimizing circumcision for female. Keywords: circumcision, Hadith, makrumah, tradition.